Nonsexist Language: A Progress Report - Kennedy, Deborah (Canadian Journal of Education/Revue canadienne de l'éducation, 1993)
What do students entering university know about inclusive language? This question led me to design a survey and distribute it to 348 students at a university in Eastern Canada. The results show that (1) students have had very little training in using nonsexist language; (2) despite being ill-informed, students have a wide range of opinions on issues of language and gender; (3) students regard it as important to know how to use nonsexist language; and (4) to this end, students should receive instruction in inclusive language usage before they get to university. Educators in elementary and secondary schools will need to take responsibility for teaching and using nonsexist language in their classrooms. Que savent les étudiants et les étudiantes au sujet du langage non sexiste à leur entrée à l’université? Cette question a amené l’auteure à mettre au point un questionnaire, qu’elle a distribué à 348 étudiants et étudiantes dans une université de l’est du Canada. Les résultats indiquent que 1) la population étudiante a peu d’expérience dans l’utilisation d’un langage non sexiste, 2) que, même si elle mal informée, elle a un vaste éventail d’opinions sur la question de la langue et du sexe, 3) qu’elle juge qu’il est important de savoir comment utiliser un langage non sexiste, et que 4) à cette fin, elle devrait recevoir une formation sur la question avant son arrivée à l’université. Les éducateurs au primaire et au secondaire devront donc voir à enseigner et à utiliser un langage non sexiste dans leurs classes.